Different characterizations of DMP-inverse of matrices. Issue 3 (11th February 2022) - Zuo, Kezheng; Cvetković Ilić, Dragana; Cheng, Yingjie
Abstract : In this paper we discuss different properties of DMP-inverse of a square matrix introduced by Malik and Thome [On a new generalized inverse for matrices of an arbitrary index. Applied Mathematics and Computation. 2014;226: 575–580]. We characterize DMP-inverse of a square matrix as an outer inverse with prescribed range and null space, as a ( B, C ) -inverse and as a Drazin inverse. Also we present several different characterizations based on its range and null space as well some algebraic ones.